Zimbabwe National Water Authority electronic record support system - Chimusinde, Tapfuma Golden (Midlands State University, 2018)
The need to develop the Zimbabwe National Water Authority Electronic Record Support System was necessitated by the lack of a fast and efficient way to search and record file entries in the records department. Various data gathering methodologies were exercised to render this research such a resounding success. These include interviews and observations to mention but a few. Various alternatives to produce the System Software were considered but fortunately at the end an in-house system software development was approved. The instruments/tools used to produce the Laptop Security System included the Barillo Barcode Software, Adobe Photoshop, MySQL, Adobe InDesign, Adobe and lastly VB.NET programming Language.